Perceived Social Support as a Buffer Against Fear of Intimacy: Evidence from Single Girls - Jorjandi Rahmatabadi, Alireza; Naqash, Zahra; Rahnama Hassanabadi, Shahnaz; Nazifi, Azam; Firuzi Moghadam, Mahsa (Psychology of Woman Journal, 2023)
Objective: This study aims to examine the relationship between perceived social support and fear of intimacy among single girls, focusing on how support from family, friends, and significant others influences fear of intimacy levels. Methods and Materials: A cross-sectional study design was utilized with 350 single girls aged 18 to 35 years. Participants completed the Fear of Intimacy Scale (FIS) and the Multidimensional Scale of Perceived Social Support (MSPSS), assessing support from family, friends, and significant others. Data were analyzed using SPSS version 27, employing descriptive statistics and linear regression analysis to explore the predictive power of perceived social support on fear of intimacy. Findings: The findings revealed a significant negative relationship between perceived social support and fear of intimacy (R² = 0.42, adjusted R² = 0.41, p < 0.01). Specifically, support from family, friends, and significant others was inversely related to fear of intimacy levels, with family support emerging as the strongest predictor (β = -0.29, p < 0.01), followed by support from significant others (β = -0.27, p < 0.01) and friends (β = -0.25, p < 0.01). Conclusion: The study concludes that perceived social support plays a crucial role in mitigating fear of intimacy among single girls. The findings underscore the importance of nurturing supportive relationships with family, friends, and significant others as a strategy for reducing intimacy fears. These insights have implications for psychological interventions aimed at enhancing perceived social support to address fear of intimacy issues.